AN ANALYSIS OF TEXTBOOK “ENGLISH IN MIND: STUDENT’S BOOK STARTER” FOR THE 7TH YEAR STUDENTS OF JUNIOR HIGH SCHOOL BASED ON MERDEKA CURRICULUM - Encik Siti Adilah; Lalu Nurtaat; Udin; Ni Wayan Mira Susanti (Program Studi Pendidikan Bahasa Inggris, 2023)
This research focuses on the analysis of a textbook intended for 7th-grade junior high school students, specifically designed according to the latest curriculum known as the Merdeka curriculum. The aim of this study was to determine the suitability of the textbook's content for 7th-grade students. The research followed a qualitative descriptive approach, utilizing content analysis as the methodology. The primary data source for this study was the English textbook